2019
DOI: 10.1159/000499546
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Endotoxin Adsorption in Two Swedish Patients with Septic Shock

Abstract: Background: Lipopolysaccharide (endotoxin) from the outer Gram-negative bacterial wall can induce a harmful immunologic response, involving hemodynamic deprivation, and is one important motor driving the septic cascade. The positively charged poly-imine ethylene layer on the oXiris membrane is capable of adsorbing negatively charged endotoxin molecules and removing them from the blood compartment. Endotoxin is detrimental and should be removed from blood. Summary: The adsorbable endotoxin fraction in blood ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…In-vitro and clinical studies using oXiris have demonstrated procalcitonin, cytokines and endotoxin reduction. 19,20,26,28 Cytokine and endotoxin reductions are shown to correlate with a reduction in vasopressor use and improvements of MAP and SOFA scores after oXiris was initiated. 21,22,29 The authors recently reported the improvement of cardiovascular SOFA score which may be associated with the improvement of monocyte and neutrophil function after endotoxin reduction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In-vitro and clinical studies using oXiris have demonstrated procalcitonin, cytokines and endotoxin reduction. 19,20,26,28 Cytokine and endotoxin reductions are shown to correlate with a reduction in vasopressor use and improvements of MAP and SOFA scores after oXiris was initiated. 21,22,29 The authors recently reported the improvement of cardiovascular SOFA score which may be associated with the improvement of monocyte and neutrophil function after endotoxin reduction.…”
Section: Discussionmentioning
confidence: 96%
“…A few clinical studies have shown that oXiris may reduce cytokines and endotoxins, improve cardiorenal function and decrease lactate and Sequential Organ Failure Assessment (SOFA) score. 18,21 28 In the absence of large randomised controlled trials, observational studies are valuable in providing insights for the practical use of these adsorbing haemofilters.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no difference between groups in vasopressor dose, ICU or hospital length of stay, or ICU or hospital mortality [91]. A recent Swedish clinical case report, in two patients with severe Gram-negative septic shock (KDIGO class 3 AKI) and verified endotoxemia, confirmed the ability of oXiris membrane to effectively adsorb endotoxins [92], thus corroborating earlier in vitro studies [93]. In another recent case report, a critically ill patient with severe sepsis secondary to a Gram-negative bacterial infection and sepsis-associated AKI was treated with CVVHDF using the oXiris set electively changed every 12 h for 3 consecutive days.…”
Section: Prescription In Sepsismentioning
confidence: 91%
“…The size of the endotoxin molecules is about 10 kDa. However, it can form aggregates up to 1,000 kDa consisting of covalently bound lipid and polysaccharide (9). Cytokines are molecules that dissolve in water and are in free form in circulation.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, high (60 kDa) or median (50 kDa) cut-off membranes are almost never used because high cut-off membranes may increase the risk of albumin loss(11). Endotoxin molecules have a size of approximately 10 kDa, but can form aggregates of up to 1,000 kDa consisting of a covalently bonded lipid and polysaccharide(9). The smaller molecular weight of the cytokines, the more cytokines will be removed in the CRRT.…”
mentioning
confidence: 99%